Large Hole Presplitting with Modified Air Gap Blast Designs in Weak Rock - Virgil J. Stachural; Matthew N. Plis; Larry R. Fletcher (International Society of Explosives Engineers, 1991)
The Bureau of Mines is conducting research on blasting methods that reduce highwall overbreak and the associated rockfall hazards. This paper presents the results of a series of tests to improve presplitting at a western surface coal mine. Reductions in overbreak were achieved by decoupling and/or repositioning the main explosive charge in the 10-5/8 inch presplit blastholes that formed the highwall. Blast designs are presented by the authors for 1) repositioning the explosive charge from a weak rock layer to a stronger rock layer, 2) decoupling with cardboard tubes in the toe region, and 3) suspending bagged powder at intervals along the length of the blasthole. About the same total quantity of explosives was used in all three test designs. It was readily apparent from periodic visual examination and photographic surveys of the highwalls that the amount of rockfall was reduced, and with a longer delay before rockfalls began, in all test areas.